2015
DOI: 10.5897/jphe2015.0741
|View full text |Cite
|
Sign up to set email alerts
|

Breast feeding initiation time and its impact on diarrheal disease and pneumonia in West Africa

Abstract: Although breast feeding (BF) is protective against infectious disease amongst children, its timing initiation effect after birth is unknown, whether immediate (<1 h), hours (>1 to <24 h) or days (>24 h).The authors examined relationships between early initiation time of BF and the prevalence of pneumonia and diarrhea in infants and under 5 children adjusting for gender, previous sibling death, maternal educational level, place of delivery and birth weight. This study utilized secondary database analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Diarrhea was more common among children who didn’t start breastfeeding within one hour immediately after birth and among children who didn’t maintain breastfeeding at the time of the survey. Other studies also reported similar findings with this study [19, 28, 43]. This might be due to the fact that children who didn’t start breastfeeding within one hour after birth and didn’t maintain breastfeeding may fail to get the benefits of colostrum, which is rich by minerals and vitamins.…”
Section: Discussionsupporting
confidence: 88%
“…Diarrhea was more common among children who didn’t start breastfeeding within one hour immediately after birth and among children who didn’t maintain breastfeeding at the time of the survey. Other studies also reported similar findings with this study [19, 28, 43]. This might be due to the fact that children who didn’t start breastfeeding within one hour after birth and didn’t maintain breastfeeding may fail to get the benefits of colostrum, which is rich by minerals and vitamins.…”
Section: Discussionsupporting
confidence: 88%
“…Of these, six papers focused on the national level, [11][12][13][14][15][16] while the other three compared associations between regions. [17][18][19] The following variables were reported as significantly associated with an increased probability of caregiver reported ARI symptoms: use of unclean cooking fuel, low wealth index, living in the North-West region (vs the South-West or South-South), dry season, lack of handwashing and living in a rural versus urban area.…”
Section: Socioeconomic and Environmental Determinants Of Arimentioning
confidence: 99%
“…Other studies have shown that mixed feeding is associated with increased diarrhea and pneumonia/respiratory diseases in children [16][17][18][19][20]. Infants who were not exclusively breastfed have a 165% higher likelihood of suffering from diarrhea and 107% higher likelihood of pneumonia than children who were exclusively breastfed [17,20].…”
Section: Introductionmentioning
confidence: 99%